The relationship between overuse injury and biomechanics in runners - McClay, I. (1999)
Running is a highly repetitive activity placing the musculoskeletal structures of the lower extremity at risk for overuse injuries. As a result of the repetitive nature of the sport, even subtle deviations in mechanics can result in the accumulation of an overuse injury. These subtle deviations are often difficult to discern, even with the technological advances that have been made in motion analysis systems. There have been literally hundreds of studies of the biomechanics of running over the past few decades. These studies are mostly descriptive in nature and have provided an initial understanding of the forces and motions the body experiences during the activity of running. However, very few of these studies include injured subjects.Therefore, these relationships between mechanics and injury are still not very well understood. Factors such as excessive excursions, high forces, excessive loading rates, and increased velocities have been suggested to be related to the overuse injuries that runners typically sustain. In addition, researchers are beginning to study the coupling of motion between joints, rather that assessing joints in isolation. Anatomical factors are also thought to play a role in abnormal mechanics. Those involved in the study of running injuries concur that injuries likely have a multifactorial etiology and predictive equations need to incorporate both structural and biomechanical variables. One of the problems we face as scientists and clinicians is determining whether the biomechanics that the injured runner presents with are the cause or the result of the injury. Prospective studies are needed to more accurately understand the etiology of these injuries. The presentation will review some of the proposed biomechanical mechanisms for overuse injuries. Where possible, research examining these mechanisms will be presented. The study of the relationship between mechanics and injuries is still in its infancy and more questions can be posed than answers given. The presentation will conclude with suggestions for future research. As the etiology of running related injuries becomes elucidated, preventative strategies can be developed so that these injury risks can be minimized.